Hydrogen Adsorption on PdGa(100), (111) and (-1-1-1) Surfaces: A DFT Study - Bechthold, Pablo Ignacio (2014)
Hydrogen adsorption on PdGa intermetallic compound is analyzed using density functional theory (DFT) calculations. Changes in the electronic structure of PdGa(100), (111) and (111) surfaces and H bonding after adsorption are addressed. H interacts with Pd atoms with a tilted geometry on (100) and (111) surfaces. On the (111) surface two possible forms for H adsorption are detected: one is observed atop perpendicular to the surface and the other one is subsuperficial, both with similar adsorption energies. The Ga-H interaction is energetically less stable and is only present on the (100) plane. Pd-Pd bond strength decreases up to 53.8% as the new Pd-H bond is formed. The Pd-H bond length differs less than 1%, compared to the gas phase value for the (100), (111) and atop (111). However in the (111) subsurface-H bond length is about 2.17 Å. The effect of H is limited to its first Pd neighbor. Analysis of orbital interaction reveals that the Pd-H bond mainly involves s-s and s-p orbitals with lower participation of Pd 4d orbitals. The computed H vibration frequencies after adsorption show values of 1786, 1289 and 633.5 cm-1 that correspond to top, bridge and hollow sites respectively.